Application of human governance by Syariah Committee in determining the Islamicity of banking products - Yusoh, Melissa Johannie (2013)
The growth of Islamic banking industry in Malaysia is evidenced with the rapid increase in the total assets of the Islamic banking sector that grew to RM434.6 billion. However, there have been strong views questioning the spirit of Islamic banking and finance, driving this study to uncover the essence of the decision making in determining the Islamicity of products embraced by the Syariah Committees. Since this study is new in nature, it adopts an interpretive approach of in-depth interviews. Based on the responce from eleven (11) Syariah Committee members, it is found that the Syariah Committee members use the guidelines as prescribed by the Bank Negara Malaysia as the sole criteria for determining the Islamicity of banking products. The study also found that riba does exist in Islamic instruments. The study also reveals that the Islamic instruments are, in essence modified from conventional banking practices. It is based on contractum trinius and do not fully attained the Maqasid. Therefore, this study concludes that there was little room for individuals to move beyond corporate governance in determining the Islamicity of banking products, thus human governance is not yet practiced by the Syariah Committee members.